Struggling Towards Coherence in Canadian Administrative Law? Recent Cases on Standard of Review and Reasonableness - Daly, Paul (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2016)
Although the Supreme Court of Canada’s seminal decision in Dunsmuir v. New Brunswick has now been cited more than 10,000 times by Canadian courts and administrative tribunals, many of its key features remain obscure. In this article, the author analyzes recent cases decided under the Dunsmuir framework with a view to determining where Canadian courts might usefully go next. The author’s argument is that the two important principles said to underlie the Dunsmuir framework—the rule of law and democracy—can provide guidance to courts in simplifying and clarifying judicial review of administrative action. In Part I, the author explains how the relationship between Dunsmuir’s categorical approach and the contextual approach that it replaced is uncertain and causes significant confusion, and explores the potential utility of the two underlying principles in simplifying the law. The application of the reasonableness standard of review is the focus of Part II, in which the author criticizes the general approach to reasonableness review in Canada, but suggests that the rule of law and democracy may assist in clarifying the law, by setting the boundaries of the “range” of reasonable outcomes and structuring the analytical framework for identifying unreasonable administrative decisions. Finally, the author draws the strands of Parts I and II together by arguing for the adoption of a unified, context-sensitive reasonableness standard, underpinned by the rule of law and democracy, with the aim of providing clarity and simplicity to Canadian administrative law in a manner faithful to the Supreme Court of Canada’s decision in Dunsmuir.